Comparative investigation on ultimate strength of hull girder with laser-welded web-core sandwich deck. (15th November 2022) - Zhong, Qiang; Wu, Guangming; Han, Zhengjun; Wang, Deyu
Abstract: This paper numerically studies the ultimate strength characteristics of the hull girder with the upper deck made of the laser-welded web-core sandwich plates subjected to the vertical bending, the horizontal bending, the torsion and the combined loads among them. The hull girder with the upper sandwich deck is designed from the typical midship section of a light cargo ship as the prototype on the basis of equal cross-sectional area. Compared with the prototype hull girder, the advantages of the hull girder with the upper sandwich deck in the ultimate strength are fully demonstrated in this paper. The results show that by using the laser-welded web-core sandwich deck, the stiffness of the hull girder under sagging has been improved. The sagging ultimate strength of the hull girder can be increased by 15%, and the horizontal bending ultimate strength can be increased by 6.2%. The finite laser weld rotation stiffness has no significant effect on the ultimate strength of the hull girder with the upper sandwich deck. Based on the numerical results, the ultimate strength interaction relationships for the hull girders under the combined two or three moments are established with high accuracy. Highlights: Sagging ultimate strength of sandwich hull girder is increased by 15% comparing with prototype hull girder. There is little effect of finite laser weld rotation stiffness on ultimate strength of sandwich hull girder. On basis of pure torsion condition, a slight increase in vertical or horizontal bending moments will not significantly reduce torsion ultimate strength of hull girder with upper sandwich deck. Ultimate strength interaction relationships for the hull girders are established with high accuracy.